Role of EEG and MRI brain in the diagnosis of unprovoked seizures in children in a tertiary care centre - Priyadarshini , Theetla; Pradheep Kumar, Kokku; CH, Sravanthi; Chaitanya Jyothi, Ravula (ScienceRise: Medical Science, 2023)
Seizure disorders are a major public health problem in a developing country like India. Epilepsy characterized by recurrent unprovoked seizures is a common heterogeneous neurological problem in children that exerts a significant medical, physical, psychological, social, and economic challenge. This study evaluated the importance of the available diagnostic modalities, EEG and MRI, which could influence the management, prognosis and recurrence of unprovoked seizures. The aims and objectives: To determine the role of Electroencephalography and MRI BRAIN in evaluating children presenting with unprovoked seizures. Methodology: The present study was a hospital-based observational study carried out during the period of January 2021 to December 2021 of 70 children who presented with unprovoked seizures to the Department of Paediatrics, Niloufer Hospital, Hyderabad. Results: Among the 70 children who were investigated, EEG showed abnormal findings in 45 (64.29 %) cases. Out of these, the majority of 32 (45.71 %) cases had generalized seizures, and 13 (18.57 %) cases were focal seizures. MRI showed abnormal findings in 30 (42.86 %) cases, and an equal percentage of cases, 15 (21.43 %) of generalized seizures and focal seizures, were having abnormal MRI findings out of the 30 cases with abnormal MRI findings. But, when studied among the individual seizure subtype, a major proportion of focal seizure (68.18 %) cases out of 22 focal seizures had abnormal MRI findings when compared to 31.25 % of generalized seizure cases out of 48 generalized seizure cases with abnormal MRI findings. Conclusion: MRI can identify most of the structural brain abnormalities, and EEG is useful to clearly identify the region of the epileptogenic foci. Therefore, EEG and MRI were useful in identifying a possible cause for unprovoked seizures in children